Towards Country-Specific Nitrous Oxide Emission Factors for Manures Applied to Arable and Grassland Soils in the UK - Thorman, Rachel E.; Nicholson, Fiona A.; Topp, Cairistiona F. E.; Bell, Madeleine J.; Cardenas, Laura M.; Chadwick, David R.; Cloy, Joanna M.; Misselbrook, Tom H.; Rees, Robert M.; Watson, Catherine J.; Williams, John R. (Frontiers in Sustainable Food Systems, 2020)
Nitrous oxide (N2O) emission factors (EFs) were calculated from measurements of emissions from livestock manures applied to UK arable crops and grassland as part of a wider research programme to reduce uncertainty in the UK national agricultural N2O inventory and to enhance regional inventory reporting through increased understanding of processes and factors controlling emissions. Field studies were undertaken between 2011 and 2013 at 3 arable and 3 grassland sites in the UK. Nitrous oxide emissions were measured following the autumn and spring application of different manures (pig slurry, cattle slurry, cattle farmyard manure (FYM), pig FYM, poultry layer manure, and broiler litter) at typical rates, using representative manure application and soil incorporation methods. In addition, ammonia emissions and nitrate leaching losses (1 site on a light sandy soil) were measured to calculate indirect N2O losses. IPCC comparable, direct N2O EFs ranged from −0.05 to 2.30% of total nitrogen applied, with the variability driven by a range of factors including differences in manure composition, application method, incorporation and climatic conditions. When data from the autumn applications were pooled, the mean N2O EF from poultry manure (1.52%) was found to be greater (P < 0.001) than from FYM (0.37%) and slurry (0.72%), with no difference found (P = 0.784) in the EF for bandspread compared with surface broadcast slurry application, and no effect (P = 0.328) of the nitrification inhibitor, Dicyandiamide (DCD). For the spring applications, the mean N2O EF for bandspread slurry (0.56%) was greater (P = 0.028) than from surface broadcast slurry (0.31%), but there were no differences (P = 0.212) in the mean N2O EFs from poultry manure (0.52%), slurry (0.44%), and FYM (0.22%). The study did confirm, however, that DCD reduced N2O emissions from slurries applied in the spring by 45%. EF data from this project have been used in the derivation of robust Tier 2 country specific EFs for inclusion in the UK national agriculture greenhouse gas inventory.